Regional-scale modeling of rainfall-induced landslides under random rainfall patterns. (September 2022) - Zhao, Lianheng; Liu, Min; Song, Zhichen; Wang, Shuguang; Zhao, Zhigang; Zuo, Shi
Abstract: The importance of rainfall patterns in triggering landslides has been recognized worldwide. In this study, the triggering and evolution of rainfall-induced landslides were investigated by a regional-scale physical model based on one-dimensional Richard equation and infinite slope model, where a bounded random cascade model (BRCM) was adopted to generate random rainfall patterns (RRPs) for rainfall events derived from extreme value analysis. The results indicated that the RRPs affect the evolution of triggered landslide and the cumulative landslide area. The shape of RRPs determined the time evolution of triggered landslide. Due to the randomness of rainfall peaks under RRPs and limited hydraulic conductivity of soil, an upper bound existed for the cumulative landslide area under RRPs and the dispersion of the cumulative landslide area increased with an increase in the return period. This study aids in the understanding of the diversity and discipline of the evolution of rainfall-induced landslides. Highlights: The influence of random rainfall patterns on the rainfall-induced landslide were investigated. The shape of random rainfall patterns determined the time evolution of the triggered landslide. An upper bound existed for the cumulative landslide area under random rainfall patterns. The dispersion of the cumulative landslide area increased with an increase in the return period.